Indonesia and Islam in Transition - Sebastian, Leonard C. author. aut Link
XXXV, 274 p. 31 illus., 22 illus. in color.
Keywords: This book focuses on Islam in Indonesia, showcasing the wide range of Muslim organisations, belief systems and movements, together with an analysis of the political behaviour of Indonesian Muslims. It includes an investigation of the structure of groups, organizations, and societies, and how Muslims within the archipelago interact within these contexts. In doing so, it promotes a more nuanced understanding of Indonesian Muslim society by approaching it through the utilisation of scholarly frameworks. Theories related to religion and society are used, especially in characterising the transition of the Indonesian Muslim society from pre-New Order to post-New Order. Particularly significant is Abdullah Saeed's framework in understanding one’s attitude towards key and contemporary issues, originally used to understand one’s attitude towards the religious ‘other’. The authors thus adopt this framework in the book, as a method of categorising people in a diverse society which in turn helps readers to understand the nuances of Islam and Muslims in a huge country like Indonesia. Dr. Leonard C. Sebastian is Senior Fellow and Coordinator of the Indonesia Programme at the S. Rajaratnam School of International Studies (RSIS). Educated at York University (Canada) and The Australian National University, his academic training is in History, International Political Economy and Strategic and Defence Studies. He has covered Indonesia in a career spanning more than two decades and published his first major work on Indonesia about defence and security doctrine titled Realpolitik Ideology: Indonesia’s Use of Military Force (2006). Syed Huzaifah Bin Othman Alkaff is a Associate Research Fellow at the Indonesia Programme at the S. Rajaratnam School of International Studies (RSIS), Nanyang Technological University (NTU), Singapore. His research interests include Middle Eastern and North African Politics, Political Islam, Islamic Jurisprudence, and Islamist Movements in Southeast Asia.